Information system curriculum design model for institutions of higher learning - Thong, Chee Ling (2015)
The Information System (IS) is important to Institution of Higher Learning (IHL) especially in the domain of curriculum design. Without the support of IS, curriculum designers in IHL faced difficulties during the curriculum design process. The difficulties include mapping of course learning outcome (CLO) to appropriate learning domains, aligning CLO to teaching and learning activities, aligning CLO to assessment tasks and meeting accreditation requirements such as student learning time. These tasks are time-consuming, error-prone and tedious. This is further confirmed by preliminary study conducted among 17 IHL in Malaysia. The findings of preliminary study show that there is a need to have an IS for curriculum design which provides step-by-step guidance in addressing issues faced by curriculum designers during the design process. The literature concludes that there are numerous Curriculum Design Information Systems, but lack of step-by-step guidance to curriculum designers. Through the review of literature, it is also discovered that agent technology has not been adopted by IS for curriculum design despite its benefits such as it helps to automate repetitive tasks, as a result reducing time, error and effort of curriculum designers during curriculum design process. The curriculum design process possesses many activities such as CLO mapping and alignment. However, research on IS model for curriculum design that provides guidance to accomplishing the tedious tasks is scarce. Therefore, the availability of an IS model that can guide and assist curriculum designers both novices and experienced ones during the design process might help in reducing time, error and effort in their design. The main goal of this research is to introduce a model namely IS Curriculum Design (ISCD) Model that provides guidance to guide and assist curriculum designers during design process. ISCD Model has the component of agent technology that is able to capture error and provide services in terms of notification and suggestions to curriculum designers so that they are guided during the design process. For this purpose, a literature study is first conducted to identify the relevant Curriculum Design Information Systems and analyze their strengths and limitations. The structure of ISCD Model is based on three basic IS activities of input-process-output (IPO). The components and subcomponents of each activity are: Input consists of internal and external input; process consists of curriculum database, curriculum design module which subscribes the services of notification agent and curriculum design process which consists of step-by-step design process; output includes alignment matrix and reports. The appropriateness and importance of these components of the model are then verified through expert review on curriculum design process in terms of its content and sequence; and survey is conducted among ninety curriculum designers in IHL on the proposed model. The results of expert review show the content and sequence of curriculum design process component are appropriate and systematic; and the findings of the survey show that all components and its subcomponents are agreed by respondents to be important and all mean scores are above 3.0. Subsequently, the ISCD Model is validated by being applied in the prototype. Then, a prototype namely Chloe’s Curriculum Design Information System (C2DIS) is developed and a survey is conducted to evaluate the usability and acceptance of the prototype. Eighty curriculum designers in IHL who have knowledge and experience on curriculum design participated in this survey. The results of the survey show that the model is useful in terms of reducing time, error and effort of curriculum designers. It is also demonstrated that ISCD Model can be beneficial to curriculum designers in guiding and assisting them throughout the curriculum design process. A technology acceptance test using Technology Acceptance Model (TAM) is conducted to explore the impact of curriculum designers’ perceptions pertaining to usefulness, ease of use, attitude towards and intention to use the system. The findings indicate that C2DIS is an easy, effective and useful system to help curriculum designers in designing curriculum. This brings about the positive frame of mind towards using the system. This leads to the conclusion that ISCD Model can be used by curriculum designers in performing their work in a systematic manner with step-by-step guide during the design process.